Nicotinic Acid-Mediated Activation of Both Membrane and Nuclear Receptors towards Therapeutic Glucocorticoid Mimetics for Treating Multiple Sclerosis - W. Todd Penberthy (PPAR Research)
Acute attacks of multiple sclerosis (MS) are most commonly treated with glucocorticoids, which can provide life-saving albeit only temporary symptomatic relief. The mechanism of action (MOA) is now known to involve induction of indoleamine 2,3-dioxygenase (IDO) and interleukin-10 (IL-10), where IL-10 requires subsequent heme oxygenase-1 (HMOX-1) induction. Ectopic expression studies reveal that even small changes in expression of IDO, HMOX-1, or mitochondrial superoxide dismutase (SOD2) can prevent demyelination in experimental autoimmune encephalomyelitis (EAE) animal models of MS. An alternative to glucocorticoids is needed for a long-term treatment of MS. A distinctly short list of endogenous activators of both membrane G-protein-coupled receptors and nuclear peroxisome proliferating antigen receptors (PPARs) demonstrably ameliorate EAE pathogenesis by MOAs resembling that of glucocorticoids. These dual activators and potential MS therapeutics include endocannabinoids and the prostaglandin 15-deoxy-Δ12,14-PGJ2. Nicotinamide profoundly ameliorates and prevents autoimmune-mediated demyelination in EAE via maintaining levels of nicotinamide adenine dinucleotide (NAD), without activating PPAR nor any G-protein-coupled receptor. By comparison, nicotinic acid provides even greater levels of NAD than nicotinamide in many tissues, while additionally activating the PPAR𝛾-dependent pathway already shown to provide relief in animal models of MS after activation of GPR109a/HM74a. Thus nicotinic acid is uniquely suited for providing therapeutic relief in MS. However nicotinic acid is unexamined in MS research. Nicotinic acid penetrates the blood brain barrier, cures pellagric dementia, has been used for over 50 years clinically without toxicity, and raises HDL concentrations to a greater degree than any pharmaceutical, thus providing unparalleled benefits against lipodystrophy. Summary analysis reveals that the expected therapeutic benefits of high-dose nicotinic acid administration far outweigh any known adverse risks in consideration for the treatment of multiple sclerosis.